2015
DOI: 10.9755/ejfa.v27i1.17971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poultry manure on the yield and nutriments uptake of potato under saline conditions of arid regions

Abstract: In hot arid lands, soil salinity, irrigation with brackish waters and the massive use of mineral fertilizers are major constraints for the development of potato cropping. The current field experiment was conducted in the Sahara Desert of Algeria in order to highlight the effect of organic fertilization on the improvement of potato production and the increase of plant salt-stress tolerance. The variation of yield production parameters and nutritional status of plants were evaluated through a split-plot design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…Other investigators reported that organic fertilization enhanced salt tolerance of some vegetable crops under saline conditions. In this regard, Oustani et al, (2015) revealed a significant and proportional increasing of all studied yield parameters of potato with the increase of poultry manure rates compared to the control under saline conditions. Chicken manure mineralized faster than alternative animal manure; hence it releases its nutrients for plant uptake and utilization rapidly.…”
Section: Plant Growth Parametersmentioning
confidence: 73%
“…Other investigators reported that organic fertilization enhanced salt tolerance of some vegetable crops under saline conditions. In this regard, Oustani et al, (2015) revealed a significant and proportional increasing of all studied yield parameters of potato with the increase of poultry manure rates compared to the control under saline conditions. Chicken manure mineralized faster than alternative animal manure; hence it releases its nutrients for plant uptake and utilization rapidly.…”
Section: Plant Growth Parametersmentioning
confidence: 73%
“…as well as total fruit yield (A+ B ton per fed.). In this respect (Oustani et al, 2015) found that the improvement of yield parameters of potato following fertilization with high rate of PM (60 m 3 ha -1 ) could be attributed to the improvement of both soil moisture retention and potentials of nutrient supply with macro and micro nutrients for the sandy soils., i.e. which it is the experiments site.…”
Section: Effect Of Organic Fertilizersmentioning
confidence: 98%
“…Application of ChM with high rates 150 and/or 120 kg N fed -1 which gave the highest values for most studied traits compared to addition of the same rates from cow manure in both seasons. (Oustani et al, 2015) on potato plant, found that the application of poultry manure at rate of 60 m 3 ha -1 produced the highest averages in all yield parameters i.e., number of tubers per plant, tuber size per plant, tuber yield per plant, and total tuber yield per ha -1 compared to adding of PM at rates of 20, 30, 40, and 50 m 3 ha -1 .,They also referred in their findings that the average of Na + contents measured in both potato leaves and roots proportionally and significantly decreased with the increase of PM rates.…”
Section: Effect Of Organic Fertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…For the improvement of irrigated WP in wheat crops under the arid and semi-arid conditions of North Africa, it is proposed to: (i) apply three to four irrigations at the appropriate time of the growth season; (ii) control weeds; (iii) apply suitable doses of fertilizer. In this context, biofertilizer is demonstrated to offer better yields and resilient adaptation to plants grown under water and salinity stresses compared to mineral fertilizer (Boudjabi et al, 2015(Boudjabi et al, , 2018Oustani et al, 2015). Nakhforoosh et al (2016) consider that WP is a component of crop resistance to water stress which determines the yield.…”
Section: Effects Of Supplemental Irrigation and Wp On Yieldmentioning
confidence: 99%